SSD for R: A Comprehensive Statistical Package to Analyze Single-System Data - Auerbach, Charles; Schudrich, Wendy Zeitlin (Research on social work practice, 2013)
The need for statistical analysis in single-subject designs presents a challenge, as analytical methods that are applied to group comparison studies are often not appropriate in single-subject research. SSD for R is a robust set of statistical functions with wide applicability to single-subject research. It is a comprehensive package of statistical tests and produces accompanying graphs for almost every function. These include, among others, tests of autocorrelation, t-tests, effect sizes, median and celeration χ2 analyses, and control charts. All functions and graphs are described in a series of tables. Since SSD for R is open source, it is freely available and can be accessed on the authors’ website, www.ssdanalysis.com. Additional support, including video tutorials and sample data are also available at no charge.